Macroeconomic Determinants of Remittances Inflow in Nepal (Quest Journal of Management and Social Sciences, 2024)
Background: The phenomenon of international migration and remittances has gained significant attention in recent years, particularly in the context of developing countries like Nepal. In 2020 alone, remittance flows to low- and middle-income countries (LMICs) reached $540 billion. In many developing nations worldwide, including Nepal, migration has become an important source of income and foreign exchange, providing critical support for households and contributing to economic growth.Objective: To investigate the effect of various macroeconomic factors on remittance inflow in Nepal.Methods:  Using the ARDL approach to co-integration, the study examines Nepal's short-run and long-run macroeconomic determinants of remittances, utilising annual data from 1993 to 2021.Results: The study finds that global oil prices, nominal exchange rate, and domestic output influence remittance inflow in Nepal. None of the macroeconomic variables affect remittance inflow significantly in the short run, while the oil price is positive and significant in the long run. The study also identifies the existence of a correction mechanism in the case of remittances whenever deviations from the long-run equilibrium occur. Furthermore, a negative association between domestic GDP and remittances corroborates the common finding that remittances are countercyclical and altruistic.Implications: The study has major policy implications, highlighting that remittance inflows are affected by external factors and that there is a negative relationship between domestic GDP and remittance inflows. These findings should be considered when formulating policies related to foreign employment and remittance inflows.Paper Types: Research PaperJEL classification: B22, F24, C22